LECLERCIA ADECARBOXYLATA, A RARE CAUSE OF SOFT TISSUE INFECTIONS IN IMMUNOCOMPROMISED PATIENTS, CASE REPORT AND REVIEW OF THE LITERATURA - Carlos A. Botero-García (Asociación Colombiana de Infectología, 2018)
Leclercia adecarboxylata is a member of the Enterobacteriaceae family that has been isolated from several environmental and animal specimens, however it rarely causes diseases in human beings. It has natural resistance to several antibiotics, and has shown the ability to harbor and produce enzymes capable of hydrolyzing most of the antibiotics used in daily clinical practice, making its treatment a challenge when a strain with such characteristics causes disease. Here we report the first known case of infection by Leclercia adecarboxylata after a trauma with plant material, in a 69-year-old male patient, with poorly controlled Diabetes Mellitus type 2.